Mengembangkan Potensi SDM Melalui Pelatihan Kewirausahaan di Desa Waluya Cikarang Utara Guna Meningkatan Jiwa Berwirausaha - Fema Chintia; Etty Zuliawati Zed; Nasywa Amelia Aura Eren; Afrilia Martina Jovanda Wewengkang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This training focuses on efforts to develop the potential of Human Resources (HR) through entrepreneurship training in North Cikarang District with the aim of increasing the entrepreneurial spirit among the local community. Entrepreneurship training is designed to provide an understanding of entrepreneurial concepts, practical skills, and motivation needed to start and manage a business. Entrepreneurship training is expected to be able to change people's mindset to be more innovative and independent in creating business opportunities. The research method used is a qualitative approach by collecting data through observation, interviews, and questionnaires with training participants and related parties. With a participatory approach and structured training, developing human resource potential can be a key factor in strengthening the local economy and increasing people's entrepreneurial knowledge, skills, and attitudes, thereby strengthening their entrepreneurial spirit. It is hoped that this positive impact can contribute to economic growth and community independence and can be developed optimally to support local economic growth through entrepreneurial activities.